Zoledronic acid and denosumab are associated with similar fracture incidence and mortality in patients with type 2 diabetes: a population-based cohort study - Rouach, Vanessa; Gortler, Hilary; Greenman, Yona; Chodick, Gabriel; Goldshtein, Inbal (Frontiers in Endocrinology, 2025)
PurposeTo assess the comparative effectiveness of zoledronic acid vs. denosumab in prevention of major osteoporotic fractures and mortality among patients with type 2 diabetes.MethodsThe study population was identified by crosslinking the diabetes and osteoporosis registries of a large healthcare organization in Israel. Demographics, Charlson Comorbidity Index (CCI), diabetes complications, bone mineral density (BMD) T-scores, hemoglobin A1c levels, eGFR, purchase of statins and anti-resorptive agents were collected. Exposure groups were matched using propensity score. Kaplan-Meier curves were generated to assess the time from treatment initiation to outcomes. Multivariable Cox’s proportional hazards survival models estimated hazard ratios (HR) and 95% CIs for each outcome.ResultsAmong 27503 patients with concurrent osteoporosis and type 2 diabetes, 627 (4.7%) received zoledronic acid and 502 (3.7%) denosumab. Prior to matching, the denosumab-treated patients were older (mean age 75.7 vs 71.9, p<0.01), had longer diabetes duration (mean 8.4 vs 7.2 years, p<0.01), and had a lower baseline eGFR (59.4 vs 75.3, p<0.01) than the zoledronic acid-treated patients. After matching, 415 pairs of subjects were included. The incidence of all examined outcomes was similar in the Zol and Dmab treatment groups, including 5-year cumulative incidence of fractures (38% vs 31%), death events (36% vs 41%), overall fracture risk (HR=1.17, 95% CI: 0.78 to 1.75), death risk (HR= 1.12, 95% CI:0.87 to 1.44), and mortality after a hip fracture (HR= 0.92, 95% CI:0.37-2.29).ConclusionsOur findings suggest comparability of Zoledronic Acid and Denosumab in managing osteoporotic fractures and mortality among patients with type 2 diabetes.